The Effectiveness of Problem-Based Learning E-Modules on Students' Science Literacy: A Systematic Literature Review - Shelliana Iqlima; Neli Yuliani; Asyil Arifah; Irman Muliadi; Salwa Salwa (Indonesian Publication Center, 2026)
Science literacy is a fundamental competency that reflects students’ ability to understand and apply science knowledge in real-world contexts. The integration of Problem-Based Learning (PBL) into digital E-Modules has emerged as a promising innovation to improve this competency. This study analyzes the effectiveness of PBL-based E-Modules on students’ science literacy through a Systematic Literature Review (SLR) with PRISMA guidelines. Ten national and international articles published between 2016 and 2025, retrieved from Google Scholar, Garuda (SINTA), and ERIC databases, were selected and analyzed. The analysis reveals a positive trend in which PBL-based E-Modules generally and effectively support the improvement of science literacy across various educational levels. Three major themes emerge: (1) effectiveness of E-Modules in enhancing science literacy indicators through multimodal and interactive content; (2) the role of PBL in stimulating scientific reasoning and authentic problem-solving; and (3) integration of contextual and ethnoscience approaches as a catalyst for meaningful learning. These findings confirm that the synergy between interactive digital media and PBL is the key mechanism for transforming students’ science literacy in 21st-century education.